2018
DOI: 10.1103/physrevb.97.054403
|View full text |Cite
|
Sign up to set email alerts
|

Quantum spin quadrumer

Abstract: A fundamental motif in frustrated magnetism is the fully mutually coupled cluster of N spins, with each spin coupled to every other spin. Clusters with N = 2 and 3 have been extensively studied as building blocks of square and triangular lattice antiferromagnets. In both cases, large-S semiclassical descriptions have been fruitfully constructed, providing insights into the physics of macroscopic magnetic systems. Here, we develop a semiclassical theory for the N = 4 cluster. This problem has rich mathematical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Our analysis of the XY quadrumer resonates strongly with the problem of the Heisenberg quadrumer. Two of the current authors have shown that the Heisenberg quadrumer possesses a non-manifold ground state space 17 . It is generically five-dimensional.…”
Section: Summary and Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our analysis of the XY quadrumer resonates strongly with the problem of the Heisenberg quadrumer. Two of the current authors have shown that the Heisenberg quadrumer possesses a non-manifold ground state space 17 . It is generically five-dimensional.…”
Section: Summary and Discussionmentioning
confidence: 88%
“…In fact, the XY CGSS is a slice of the Heisenberg ground state space. Remarkably, in the Heisenberg problem, the low-energy states do not consist of bound states, and a good effective description is obtained by neglecting singularities 17 . This suggests that not all non-manifolds can induce bound states.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is minimized in configurations where the sum of four spins vanishes. The set of all such states has been shown to form a non-manifold space that is generically five-dimensional 33 . Here, as seen from Tab.…”
Section: Summary and Discussionmentioning
confidence: 99%

Order by singularity in Kitaev clusters

Srinivasan,
Khatua,
Baskaran
et al. 2019
Preprint
Self Cite